The development of the Roman alphabet and its implications for handwriting comparison in the British/Irish sphere - Craythorne, Brian (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The development of the alphabet from about 2000 BC to the modern age has interesting implications in the work of forensic handwriting analysts. This overview provides background knowledge for the forensic handwriting expert as to why some letter designs are more useful than others when it comes to handwriting comparisons. Numerals are also considered. The overview is directed for the alphabet as used in the British and Irish spheres, but can be extrapolated to other localities.
Keywords: badanie pisma ręcznego; warunki historyczne; funkcje graficzne; rozwój pisma ręcznego; istotne cechy